Fermented Jussara: Evaluation of Nanostructure Formation, Bioaccessibility, and Antioxidant Activity - Giaconia, Michele Amendoeira; Ramos, Sergiana dos Passos; Fratelli, Camilly; Assis, Marcelo; Mazzo, Tatiana Martelli; Longo, Elson; de Rosso, Veridiana Vera; Braga, Anna Rafaela Cavalcante (Frontiers in Bioengineering and Biotechnology, 2022)
The jussara (Euterpe edulis Mart.) stands out for the contents of bioactive compounds present in its composition that can be improved trough several processes, such as fermentation. In addition, considering the maintenance of the features of bioactive compounds, especially after digestive process, the nanotechnology resources can potentially solve this issue. The present work focused on tailoring nanostructures by applying polyethylene oxide, assembling fermented jussara pulp nanofibers (NFs) to assess their characteristics and measure the bioaccessibility of bioactive compounds when mixed with polymeric solution. The results revealed the formation of fermented jussara NFs with a diameter of 101.2 ± 26.2 nm. Furthermore, for ABTS and ORAC methods, the remaining percentage of antioxidant activity was 83.4% and 67.4%, respectively, which allow stating that it is possible to maintain the antioxidant activity after fermentation processes in the face of adversity of the digestive system.